Identification and expression analysis of the apple (Malus × domestica) basic helix-loop-helix transcription factor family - Jinhua Yang; Min Gao; Li Huang; Yaqiong Wang; Steve van Nocker; Ran Wan; Chunlei Guo; Xiping Wang; Hua Gao (Scientific Reports, 2017)
Abstract Basic helix-loop-helix (bHLH) proteins, which are characterized by a conserved bHLH domain, comprise one of the largest families of transcription factors in both plants and animals, and have been shown to have a wide range of biological functions. However, there have been very few studies of bHLH proteins from perennial tree species. We describe here the identification and characterization of 175 bHLH transcription factors from apple (Malus × domestica). Phylogenetic analysis of apple bHLH (MdbHLH) genes and their Arabidopsis thaliana (Arabidopsis) orthologs indicated that they can be classified into 23 subgroups. Moreover, integrated synteny analysis suggested that the large-scale expansion of the bHLH transcription factor family occurred before the divergence of apple and Arabidopsis. An analysis of the exon/intron structure and protein domains was conducted to suggest their functional roles. Finally, we observed that MdbHLH subgroup III and IV genes displayed diverse expression profiles in various organs, as well as in response to abiotic stresses and various hormone treatments. Taken together, these data provide new information regarding the composition and diversity of the apple bHLH transcription factor family that will provide a platform for future targeted functional characterization.